2014
DOI: 10.1209/0295-5075/108/17012
|View full text |Cite
|
Sign up to set email alerts
|

Spin-glass–like ground state and observation of exchange bias in Mn 0.8 Fe 0.2 NiGe alloy

Abstract: The ground-state magnetic properties of a hexagonal equiatomic alloy of nominal composition Mn0.8Fe0.2NiGe were investigated through dc magnetization and heat capacity measurements. The alloy undergoes a first-order martensitic transition below 140 K with simultaneous development of long-range ferromagnetic ordering from the high-temperature paramagnetic phase. The undoped compound MnNiGe has an antiferromagnetic ground state and it shows martensitic-like structural instability well above room temperature. Fe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…4 EBE is defined as the shift in the center of the M (H) isotherm while cooled in presence of external H. 4,22,23 EBE is particularly important because of its application in various technological fields, such as permanent magnets, magnetic recording media, sensors, and read heads.…”
Section: ∂M ∂T Hmentioning
confidence: 99%
See 2 more Smart Citations
“…4 EBE is defined as the shift in the center of the M (H) isotherm while cooled in presence of external H. 4,22,23 EBE is particularly important because of its application in various technological fields, such as permanent magnets, magnetic recording media, sensors, and read heads.…”
Section: ∂M ∂T Hmentioning
confidence: 99%
“…and their derivatives have attracted renewed attentions for the observation of fascinating magneto-functional and physical properties such as, large magneticaloric effect (MCE), exchange bias effect (EBE), spin glass (SG) like ground state etc. [1][2][3][4][5][6][7][8][9][10][11][12] Among various members of MEAs, MnNiGe is one of the potential candidates which undergoes a first-order diffusionless structural phase transition, known as martensitic phase transition (MPT), at 470 K during cooling and orders spiral antiferromagnetically below 346 K. 1,3,4,8 Physical and chemical pressures are the two most influencing parameters that can affect the physical properties of these materials simply by modifying structural parameters like lattice volume, bond angle etc. 8,13,14 Among these two, chemical pressure approach (different doping studies) is much popular among the researchers due to easy sample preparation and measurement options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, magnetic equiatomic alloys (MEAs) of general formula MM X ′ (M, M transition ′ = metals, X ¼Si, Ge, Sn) have attracted renewed interest due to the observation of various magneto-functional properties, such as magnetic shape memory effect, exchange bias and large magnetocaloric effect [8][9][10][11][12][13]. The first-order diffusionless structural phase transition, called the martensitic phase transition (MPT), is the key to this functional behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that Fe doping in Mn or Ni site induces ferromagnetism in otherwise antiferromagnetic alloy [11,16]. It has been found that Fe doping in tandem with the first order structural phase transition can give rise to coexisting fractions of ferromagnetic and antiferromagnetic phases and allows the samples to have large tenability under an applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%